Application of scenario simulation teaching method in the teaching of perioperative nursing of total knee arthroplasty (情景模拟教学法在人工全膝关节置换术围手术期护理教学中的应用) - CHEN Huiying (陈慧颖); TIAN Li (田丽); ZHANG Tianqiang (张天强) (中西医结合护理)
Objective To evaluate the scenario simulation teaching method in the teaching of perioperative nursing of total knee arthroplasty (TKA). Methods A total of 10 nursing students with internship from January to December 2019 were included as the control group, and routine teaching method was adopted in the clinical practice; Another 10 nursing students with internship from January 2020 to January 2021 were recruited as the observation group, and a scenario simulation teaching method was used in the teaching of TKA perioperative nursing . The scores of theoretical and practical assessments at the end of internship were compared between two groups. The nursing students’ opinions on scenario simulation teaching method were recorded. Results The theoretical assessment score in the observation group was higher than that in the control group (93. 90±0. 99 vs. 80. 30±1. 70, P<0. 01). The practical assessment score in the observation group was higher than that in the control group (94. 30±1. 25 vs. 81. 10±1. 20, P<0. 01). Students in the observation group had rated the teaching method highly. Conclusion By creating a friendly academic atmosphere and arousing studying interest, the scenario simulation teaching method is effective to improve nursing students’ knowledge and practice skills of TKA perioperative nursing, and eventually improving the quality of orthopedic nursing. (目的 探讨情景模拟教学法在人工全膝关节置换术围手术期护理教学中的应用效果。方法 将2019年1月—12月骨科护理实习生10人设为对照组, 将2020年1月—2021年1月骨科护理实习10人设为观察组。对照组实施传统教学法, 观察组采用情景模拟教学法。比较两组教学后理论和实践考核评分, 记录观察组护理实习生对情景模拟教学法的认可情况。结果 观察组理论成绩为(93. 90±0. 99)分、临床实践操作考核成绩为(94. 30±1. 25)分, 高于对照组的(80. 30±1. 70)分和(81. 10±1. 20)分, 差异有统计学意义(P<0. 01)。观察组护理实习生对情景模拟法较为认可。结论 情景模拟法应用于临床教学可以营造简单轻松的学习氛围, 激发护理实习生的学习工作兴趣, 有助于护理实习生牢记相关知识, 掌握相关操作, 最终提高护理质量。)